Tobacco Control Interventions during Last Decade in India: A Narrative Review - Swapnil A Gadhave; Aarti Nagarkar (Medsci Publications, 2017)
Background: Various national level surveys, Global Adult Tobacco Survey (GATS) and Global Youth Tobacco Survey (GYTS) in different age groups have shown that tobacco addiction is prevalent across age, sex and geospatial distribution. In 2007-08, Government of India piloted a National Tobacco Control program which has suggested monitoring of tobacco control laws along with local IEC activities and school program for tobacco control. Purpose of review: Objective of the current review was to identify these tobacco control interventions whose efficacies have been recently proved among Indian population. Findings: The review paper is based on the synthesis of the results of 24 studies describing interventions. Review has showed that there is a lack of standardized and robust tool to measure efficacy of the tobacco use, prevention and intervention. Interventions have used social cognition theory, extensively. Studies focused on cessation of tobacco, generally lack any theoretical framework. These studies have used self reported tobacco quit rates rather than established sophisticated tools. Conclusion: Review suggested that intervention package for community based trial should use more standardized tools to measure their outcome and can be benefitted from the use of more diverse theoretical framework for formulation of interventions.